Does the EU have a substitute for a constitution? The rule of law and common identity - Kolczyńska, Magdalena (Vilnius University Open Series, 2020)
Constitution, like no other legal act, is the manifestation of what a community thinks of itself; what are its aims, values and priorities. But what if this common source of identity is lacking? Can a body politic exist without constitution? If yes – does it come at certain price? Over a decade after the failure of a constitutional project for Europe I would like to ask whether EU has any substitute for the constitution for the following 10 years. I will consider that questions from two different standpoints – the rule of law and common European identity. First, I will ask whether existing legal order of EU needs the constitution to be consistent with the rule of law principle. This question was of great importance in Poland, as this decade started in our country with the EU triggering Article 7 of the Treaty of EU with the charge of breaching by Polish government the principle in question. The recent events however have drastically changed the situation in European Community. The observance of the rule of law does not seem enough for EU to assert its legitimacy in the course of the ongoing turmoil caused by the pandemic. What is needed is unprecedent solidarity among European Citizens – solidarity which transgress the demands of mere justice. I will claim that to maintain solidarity a common identity may be necessary. Thus, I will ask whether the constitution is necessary for the forming of European identity and whether it would be enough to achieve this aim.